MAPPING THE KNOWLEDGE OF ANEMIA AMONG FEMALE ADOLESCENTS LIVING IN RURAL AREA OF WEST TIMOR - Christina Nayoan (Medika Alkhairaat: Jurnal Penelitian Kedokteran dan Kesehatan, 2023)
Anemia is a serious global problem in society, especially in adolescents. Anemia in adolescent girls is still quite high. Knowledge is the result of knowing, occurs after people do sensing of a particular object. Knowledge is a very important domain in shaping a person's actions. This study aimed to map the knowledge about Anemia among adolescent girls who live in rural area of West Timor. A cross-sectional survey study was conducted on 156 adolescent female students of grade seven and eight at two junior high schools in Kupang regency. The sampling technique used was stratified random sampling. The results of this study showed that young females have limited knowledge about Anemia, especially knowledge regarding the definition, causes, effects and symptoms of Anemia. In conclusion the implication of this study is that adolescent girls should be give information about Anemia, thus, will deepen their knowledge about Anemia. Sufficient knowledge and practice healthy behavior will help adolescents in their lifetime and for their future. In turns, the growth and development of adolescents will be free from various problems and other health risks.